The effects of a mobile gamification app on elementary students' Spanish achievement and self-efficacy - Rachels, Jason R.; Rockinson-Szapkiw, Amanda J. (Computer assisted language learning, 2018)
A quasi-experimental, pretest-posttest, non-equivalent control group design was used to examine the effect of a mobile gamification application on third and fourth grade students' Spanish language achievement and student academic self-efficacy. In this study, the treatment group's Spanish language instruction was through the use of Duolingo®, a computer and mobile app that uses gamification and adaptive learning technology to teach foreign languages. Students in the control group received their regularly scheduled English L1/Spanish L2 class learning activities. The study was 12 weeks in duration. Students were assessed with a 50-question, multiple-choice English to Spanish and Spanish to English pretest covering vocabulary and grammar to control for prior Spanish language achievement. Students were assessed with the Pattern of Adaptive Learning Scales' (PALS) Academic Efficacy subscale to control for prior academic self-efficacy. The same two instruments were used as posttests. An analysis of covariance showed no significant difference in students' Spanish achievement or in academic self-efficacy between students who used Duolingo® and students who were taught with traditional face-to-face instruction. This demonstrates that Duolingo® is a useful tool for teaching Spanish to elementary students.